Synergetic approach to religious knowledge and its specific aspects in the formation of “husni-khulk” - Nematova Orzigul Akhmedovna (Zien Journals, 2025)
This article analyzes the role of religious knowledge in the formation of “husni-khulk” and its synergistic properties. In the content of the article, religious values, moral norms, and the process of internal harmony formed in human consciousness are considered as an interconnected system. Based on a synergetic approach, good character is interpreted as the result of complex connections between human thinking, faith, belief, and the social environment. The study highlights the influence of religious knowledge on the moral maturity of the individual, social responsibility, and mental stability. Also, the goal is to reveal from a philosophical point of view the interaction of religious teachings in the formation of “husni-khulk”, the mechanisms of self-organization.
Keywords: husni-khulk; religious knowledge; synergetics